Environmental management in Uganda: A reflection on the role of NEMA and its effectiveness in implementing Environment Impact Assessment (EIA) of the Greater Kampala Metropolitan Area (GKMA) - SSALI ISMAIL (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: This research aimed to examine how effectively the National Environment Management Authority (NEMA) implemented an Environment Impact Assessment (EIA) for the Greater Kampala Metropolitan Area (GKMA).Method: The study used a qualitative document review approach to learn more about EIA’s function and settlement occupant’s reactions to its enforcement in GKMA. Actor-Network Theory was employed to investigate the interplay of the factors.Findings: The results reveal that NEMA took on characteristics of a centralized and decentralized institution during different phases of EIA implementation and enforcement. Internal weaknesses such as a lack of skilled personnel, corruption, and poor implementation tactics were major reasons why the centralized approach to NEMA was less effective than the decentralized approach.Implications/Novel Contribution: Recent research provides an overview of NEMA’s regulatory structure. The study also covered the application of Actor-Network Theory to EIA in entrepreneurship setups.